Presentation - Sobrinho, Asdrúbal Borges Formiga; Sanmartin, Stela Maris; Cirilo, Aparecido José (Farol, 2024)
The Postgraduate Program in Arts at the Federal University of Espírito Santo is the only master's and doctoral program in the state that has a research line dedicated to the study of Creativity and Innovation, a key action in the training of cultural agents, as well as the community interested in current debates in the area. To this end, the Program has strived to maintain constant contact between its professors and students with the international research scene in Creativity and Innovation. Among its strategies, it has promoted national and international events that aim to give visibility and promote the expansion of knowledge generated by its faculty and students, creating opportunities for cooperation with various sectors of local, national and international culture and, therefore, expanding the reach and impact of the work of researchers in the area. For this reason, it has entered into a partnership with the Brazilian Association of Creativity and Innovation (Criabrasilis), which brings together specialists from the most diverse areas of knowledge, to hold the 4th International Congress of Creativity and Innovation (4th CICI) with the endorsement of the Universidad Autónoma de Madrid and the University of Minho.